Tension Strength Prediction of Transverse Branch Plate-to-Rectangular Joint with Concrete Filling - Zhihua Xiong; Yongjian Liu; Bin Liu; Lei Jiang (Fracture and Structural Integrity)
This paper predicts the tension strength of Concrete-filled Branch Plate-to-Rectangular Hollow (CBPRH) joint by conducting experimental and theoretical analysis. A total of 46 X-joints with different geometric parameters were investigated, in which 4 specimens were tested under ultimate tension and 42 specimens were numerically analyzed. The joint’s strength, failure mode and load-displacement curve were obtained. Perfobond Leister Rib (PBR) was welded in part of the specimens to investigate its effect on joint’s tensile performance. It is shown that the ultimate strength of transverse CBPRH joint benefit from grouting of chord and installation of PBR. The ultimate strength of CBPRH joint with PBR is larger than the counterpart without PBR. Tension strength equations were proposed for both CBPRH joints with and without PBR by nonlinear regression. The chord axial stress reduction factor was discussed and a modified equation originated from hollow joint was recommended for CBPRH joint. Connection efficiency was presented and compared among branch plate-to-rectangular hollow (BPRH) joint, CBPRH joint and CBPRH joint with PBR.